The Emerging Role of Gasotransmitters in the Pathogenesis of Tuberculosis - Chinta, Krishna C (Nitric Oxide, 2016)
Mycobacterium tuberculosis (Mtb) is a facultative intracellular pathogen and the second largest contributor to global mortality caused by an infectious agent after HIV. In infected host cells, Mtb is faced with a harsh intracellular environment including hypoxia and the release of nitric oxide (NO) and carbon monoxide (CO) by immune cells. Hypoxia, NO and CO induce a state of in vitro dormancy where Mtb senses these gases via the DosS and DosT heme sensor kinase proteins, which in turn induce a set of ~47 genes, known as the Mtb Dos dormancy regulon. On the contrary, both iNOS and HO-1, which produce NO and CO, respectively, have been shown to be important against mycobacterial disease progression. In this review, we discuss the impact of O(2), NO and CO on Mtb physiology and in host responses to Mtb infection as well as the potential role of another major endogenous gas, hydrogen sulfide (H(2)S), in Mtb pathogenesis.